Resource and Environment Constraints and Promotion Strategies of Rural Vitality: An Empirical Analysis of Rural Revitalization Model Towns - Yang, Zhiheng; Liu, Tiantian; Shen, Nengneng; Guan, Mei; Zheng, Yanfeng; Jiang, Huailong (Frontiers in Environmental Science, 2022)
In response to the challenges of rural chronic poverty caused by insufficient self-development ability, establishing a development model conducive to poverty alleviation and stimulating rural development potential have become core tasks of deepening rural revitalization. Resources and environment play an important role in invigorating rural vitality. Based on symbiosis theory, we have constructed a new conceptual framework to analyze dynamic performance of rural areas in population, industry and facilities and dynamic constraints in resources and environment. Using improved TOPSIS evaluation method and panel Tobit model, we have selected 106 rural revitalization model towns from Shandong province as research samples, empirically analyzed performance of rural vitality and its resources and environment constraints, explored differences of rural vitality performance and vitality constraints of different village types, and put forward long-term mechanisms to maintain rural vitality. Results shows that, from 2012 to 2019, rural vitality of rural revitalization model towns in Shandong province was gradually improved, among which industrial development had contributed the most; agriculture-tourism towns are more dynamic than industrialized agriculture towns and characteristic agricultural towns. Through analysis of resources and environment constraints on rural vitality, we found that resources had the greatest impact on rural vitality, and the short-term constraints of total amount restriction on rural vitality were not obvious; binding force of ecological environment on rural vitality changed from weak to strong, and increasingly became the “bottleneck restricting rural vitality. We have further proposed a long-term mechanism to stimulate rural vitality from the aspects of promoting comprehensive utilization of rural residential land, strengthening concept of ecological priority and green development, taking the road of urban-rural integration and promoting integrated development of rural industries.